Sera of patients with systemic lupus erythematosus cross-neutralizes dengue viruses - Zainal, Nurhafiza; Tan, Kim Kee; Johari, Jefree; Hussein, Heselynn; Wan Musa, Wan Rosmaiza; Hassan, Jamiyah; Lin, Yee-Shin; AbuBakar, Sazaly (Wiley, 2018)
Dengue is the most prevalent mosquito-borne disease in Southeast Asia, where the incidence of systemic lupus erythematosus (SLE) is approximately 30 to 53 per 100,000. Severe dengue, however, is rarely reported among individuals with SLE. Here, whether sera of patients with SLE cross-neutralize dengue virus (DENV) was investigated. Serum samples were obtained from individuals with SLE who were dengue IgG and IgM serology negative. Neutralization assays were performed against the three major DENV serotypes. Of the dengue serology negative sera of individuals with SLE, 60%, 61% and 52% of the sera at 1/320 dilution showed more than 50% inhibition against dengue type-1 virus (DENV-1), DENV-2 and DENV-3, respectively. The neutralizing capacity of the sera was significantly greater against DENV-1 (P < 0.001) and DENV-3 (P < 0.01) than against DENV-2 (P < 0.05). Neutralization against the DENV correlated with dengue-specific IgG serum titers below the cut-off point for dengue positivity. Depletion of total IgG from the sera of patients with SLE resulted in significant decreases of up to 80% in DENV inhibition, suggesting that IgG plays an important role. However, some of the SLE sera was still able to neutralize DENV, even with IgG titers <0.1 OD absorbance. Our findings suggest that sera of patients with SLE contain IgG, and possibly other type of antibodies, that can cross-neutralize DENV, which may explain the rarity of severe dengue in individuals with SLE. Further studies, are needed to further substantiate this finding and to elucidate the specific neutralizing epitopes recognized by the sera of individuals with SLE.